Development of a Structured Competency Training Program for Coast Guard Non-Maritime Junior Billet Officers - Cabral, Sean Jayner D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The Philippine Coast Guard (PCG), as the premier national agency responsible for maritime safety, security, and marine environmental protection, relies on competent shipboard officers and seaworthy vessels to achieve mission readiness and success. However, many shipboard officers lack collegiate maritime education, creating challenges amid the PCG Modernization Program. This study developed a competency-based training program to enhance the shipboard capabilities of these non-maritime officers. Using a mixed-method design, it surveyed Junior Shipboard Operational Level Course (JSOLC) instructors to evaluate course effectiveness, interviewed PCG commanding officers and merchant marine masters/chief engineers for insights on essential watchstanding competencies and best practices, and tested 49 current non-maritime officers on their knowledge and understanding of watchstanding and Coast Guard-specific protocols. The findings revealed strengths in PCG customs and protocols but significant gaps in collision regulations, navigation, marine engineering, and practical shiphandling. These deficiencies underscore the need for targeted training to align skills with operational demands. Based on the results, a structured competency-based training program was developed to address these gaps, improving shipboard efficiency and supporting mission success. The program emphasizes practical modules in navigation, shiphandling, and engineering, supplemented by STCW-aligned assessments. This contributes to competency-based training literature by highlighting education-job mismatch in Coast Guard-maritime contexts and offers practical recommendations for PCG shipboard curriculum enhancement.